Construction Waste: A Comparative Study between Conventional and Prefabrication Construction Method - Chai, Christina Lee na (2015)
Issue of construction waste is getting serious in the recent years. The generation of waste in construction industry will soon affect to the environmental issue. The rate of the wastage level is relatively high in Malaysia. The method of construction used in constructing a building is crucial as it can help to reduce the generation of material waste. In line with this, the study is carried out to analyse the types of construction waste in conventional method and prefabrication method and investigate the level of material wastage between conventional method and prefabrication method. The scope of this study mainly focuses on the contractor’s firm registered under Construction Industry Development Board (CIDB) located in Kuala Lumpur. This study is conducted by using questionnaire survey. The data were obtained and analysed by using frequency analysis, average index analysis and mean analysis. From the study the top three types of material were analysed which are timber formwork, concrete and steel reinforcement. According to the comparison of wastage level between conventional method and prefabrication method, the best method in producing less material waste is prefabrication method.